2008
DOI: 10.4028/www.scientific.net/msf.600-603.1047
|View full text |Cite
|
Sign up to set email alerts
|

1200-V, 50-A, Silicon Carbide Vertical Junction Field Effect Transistors for Power Switching Applications

Abstract: High-voltage normally-on VJFETs of 0.19 cm2 and 0.096 cm2 areas were manufactured in seven photolithographic levels with no epitaxial regrowth and a single ion implantation event. A self aligned guard ring structure provided edge termination. At a gate bias of -36 V the 0.096 cm2 VJFET blocks 1980 V, which corresponds to 91% of the 12 μm drift layer’s avalanche breakdown voltage limit. It outputs 25 A at a forward drain voltage drop of 2 V (368 A/cm2, 735 W/cm2) and a gate current of 4 mA. The specific on-resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Unclamped inductive switching (UIS) testing is a common method to evaluate device breakdown characteristics. Avalanche energies of 20.4 mJ for a SiC 1200 V/5 A BJT, 350 mJ for a 1200 V SiC JFET in the cascode configuration, and 500 mJ for a 1200 V/20 A SiC DMOSFET, have been reported [4]- [6]. In the initial phase of this paper, single pulse UIS energy of 621 mJ was reported for a 1200 V/13 A SiC JFET at a gate voltage of −20 V [7].…”
mentioning
confidence: 76%
“…Unclamped inductive switching (UIS) testing is a common method to evaluate device breakdown characteristics. Avalanche energies of 20.4 mJ for a SiC 1200 V/5 A BJT, 350 mJ for a 1200 V SiC JFET in the cascode configuration, and 500 mJ for a 1200 V/20 A SiC DMOSFET, have been reported [4]- [6]. In the initial phase of this paper, single pulse UIS energy of 621 mJ was reported for a 1200 V/13 A SiC JFET at a gate voltage of −20 V [7].…”
mentioning
confidence: 76%
“…Stephani et al reported on a lateral channel normally-on VJFET of 0.235 cm 2 active area, capable of blocking 1400 V with an associated specific on-state resistance of 10 mΩ cm 2 [12]. In this section, we present a normally-on 4H-SiC vertical-channel JFET with an active area of 0.143 cm 2 and a blocking-voltage capability of 1680 V [23,49,50]. These JFETs can be utilized as power switches with inherently safe normally-on gate-drive circuits [51].…”
Section: Thermal Properties Of Vjfet/cascodementioning
confidence: 93%
“…In this paper, we focus on the static and dynamic voltage balancing of multiple SiC VJFETs in series while switching inductive loads. In particular, we investigate a particular type of VJFET, in which the channel is vertical as in [3], rather than lateral as in [4]. The difference is seen in the balance between the Miller capacitance and the drain-source capacitance, which effects mainly gate drive considerations during dynamic voltage blocking.…”
Section: Introductionmentioning
confidence: 99%
“…Thus absolute voltage ratings might increase, leading to attractive system advantages. Indeed 1200-1500 V vertical junction field effect transistors with robust performance and low on-resistance are now available [3][4]. The fabrication of such devices into modules in series combinations to multiply voltage ratings [5] and in parallel combinations to multiply current ratings [6] have been reported.…”
Section: Introductionmentioning
confidence: 99%